The spatiotemporal dimension of population change in Ireland: visualisation of growth and shrinkage in Irish Electoral Divisions (1986–2016). Issue 3 (1st December 2022) - O'Driscoll, Josh; Meredith, David; Crowley, Frank; Doran, Justin; O'Shaughnessy, Mary; Zimmermann, Jesko
ABSTRACT: Population shrinkage has gained attention from academics and policymakers in recent years, due to the long-term implications the phenomenon has for public service delivery and the viability of urban and rural communities. We visualise the socio-temporal evolution of population shrinkage and growth, utilising a spatially rectified dataset containing population data from seven Census of Population covering the 1986–2016 period in the Republic of Ireland. Spatial changes in population distribution are visualised in a map that classifies small administrative units using a spatial typology distinguishing between those experiencing population growth or shrinkage, across the 30-year period. The temporal dimensions of these developments are considered in a sequence of inset maps that apply the same typology to identify the intercensal changes. Overall, the map facilitates the visual communication of long-run population trends, the identification of areas experiencing limited or no growth, and indicates the relative consistency of these trends over time.